2020
DOI: 10.3390/ph13120455
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Herbal Medicine Use during Palliative Cancer Care: The Integrative Physician as a Facilitator of Pharmacist–Patient–Oncologist Communication

Abstract: Oncology patients frequently use herbal and other forms of complementary medicine, often without the knowledge of oncologists, pharmacists, and other healthcare professionals responsible for their care. Oncology healthcare professionals may lack the knowledge needed to guide their patients on the safe and effective use of herbal medicinal products, a number of which have potentially harmful effects, which include direct toxicity and negative herb–drug interactions. The current review addresses the prevalence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Although there are few studies on the interaction and safety of HMs (Samuels & Ben-Arye, 2020), the results of our meta-analysis showed that the efficacy of the combination of HMs and Western medicine group was better than that of the Western medicine group, indicating that the simultaneous use of HMs would not cause serious toxic reactions or reduce the efficacy of western medicine.…”
Section: Discussionmentioning
confidence: 71%
“…Although there are few studies on the interaction and safety of HMs (Samuels & Ben-Arye, 2020), the results of our meta-analysis showed that the efficacy of the combination of HMs and Western medicine group was better than that of the Western medicine group, indicating that the simultaneous use of HMs would not cause serious toxic reactions or reduce the efficacy of western medicine.…”
Section: Discussionmentioning
confidence: 71%
“…These studies have been followed by the creation of clinical practice guidelines, recommendations, and training programs geared toward improving patient-HCP communication in the IO setting [22][23][24][25]. Little research has been conducted addressing other communication-related aspects of the IO setting, such as that between the oncology healthcare provider and IO practitioner, within the context of traditional medicine [26]; IP-patient communication in the IO setting [27], including where the IP is also a PCP [28]; and communication between the IO practitioner and oncology physician [29], nurse [30], psycho-oncologist [31], and pharmacist [32]. In the primary care setting, the PCP may also play a role as one of the patient's oncology healthcare providers, in both a medical as well as supportive and palliative care capacity.…”
Section: Discussionmentioning
confidence: 99%
“…According to available evidence from this study, AMP acceptance of TM and allowing it to be freely addressed in a non-judgemental manner may develop trust and enable disclosure to promote safe and dependable treatments for patients [ 47 , 48 ]. Other studies have found that patients who take both TM and AM should reveal their TM use to improve their overall treatment outcomes [ 49 , 50 ]. AMPs, on the other hand, should embrace their patients’ decisions to use TM and endeavour to give them all of their available options because they, too, are people with diverse perspectives [ 51 ].…”
Section: Discussionmentioning
confidence: 99%